Monitoring of avian influenza cases based on the detection of viral antigen subtype H5N1 by immunohistochemical technique - Rini Damayanti; N.L.P.I Dharmayanti; R. Indriani; A. Wiyono; R.M.A Adjid (Jurnal Ilmu Ternak dan Veteriner, 2005)
Monitoring on the cases of Avian Influenza virus was conducted by detecting viral antigen subtype H5N1 usingimmunohistochemical technique. A total of 212 sampels of various avian tissues were collected from the Provinces of East Java(Districts of Madiun, Tulung Agung, Blitar and Kediri), West Java (Districts of Bogor, Bekasi, Cianjur and Sukabumi), Banten(Districts of Pandeglang and Tangerang) and DKI Jakarta. The sampels were collected four times i.e. June 2004, September2004, October 2004 and between January and February 2005. All sampels were stained using immunohistochemical technique.The antigen could be visualized clearly both in the intra-nuclear and intra-cytoplasmic areas of brain, comb, wattle, trachea,lung, heart, breast and thigh muscle, proventriculus, liver, spleen, kidney, intestine and ovary. A number of 39 of 212 cases(18.4%) have been catagorized as positives. The results show that monitoring of HPAI cases conducted in June and September2004 in the Provinces of West Java, Banten and East Java, none of the sampels were positive. However, monitoring of thedisease in September 2004 in the Province of Jakarta showed that AI virus antigen were detected in various organs of chickenfrom Jakarta. Furthermore, monitoring of the disease conducted between October 2004 and February 2005 revealed that AI virusantigen were also detected in chicken not only from Jakarta Provinces but also from Provinces of Banten and West Java. Basedon these results, it is concluded that between June and September 2004, HPAI infection were not found in areas where previousoutbreaks occured in the Provinces of Banten, West Java and East Java. However, the disease was spread in Jakarta Province inSeptember 2004 and subsequently to some districts in the Provinces of Banten and West Java. A part from this, anticipation ofdisease spread to currently AI-free areas should be considered as part of disease monitoring system.Key Words: Avian Influenza, H5N1, Monitoring, Immunohistochemistry, Poultry